2022
DOI: 10.1128/msystems.00230-21
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Riboside-Conditioned Microbiota Deflects High-Fat Diet-Induced Weight Gain in Mice

Abstract: With obesity and type 2 diabetes (T2D) at epidemic levels, we need to understand the complex nature of these diseases to design better therapeutics. The underlying causes of both obesity and T2D are complex, but both are thought to develop, in part, based on contributions from the gut microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
0
12
0
1
Order By: Relevance
“…However, the observed increased abundance in Clostridium class is not a direct indicator of butyrate production. Previously, Lozada-Fernandez et al (2022) found similar results, demonstrating that NR-treated mice had an increase in fecal propionate, butyrate, valerate and isobutyrate concentrations compared to controls while having an increased population of Firmicutes (oxidizing butyrate for growth) [ 65 ]. This result was hypothesized to be caused by Firmicutes metagenome-assembled genomes (MAGs) utilizing acetyl coenzyme A (acetyl- CoA) butyrate synthesis pathway, thus indicating the NR supplementation enriches butyrate-producing Firmicutes (e.g., Clostridium sp.)…”
Section: Discussionmentioning
confidence: 55%
“…However, the observed increased abundance in Clostridium class is not a direct indicator of butyrate production. Previously, Lozada-Fernandez et al (2022) found similar results, demonstrating that NR-treated mice had an increase in fecal propionate, butyrate, valerate and isobutyrate concentrations compared to controls while having an increased population of Firmicutes (oxidizing butyrate for growth) [ 65 ]. This result was hypothesized to be caused by Firmicutes metagenome-assembled genomes (MAGs) utilizing acetyl coenzyme A (acetyl- CoA) butyrate synthesis pathway, thus indicating the NR supplementation enriches butyrate-producing Firmicutes (e.g., Clostridium sp.)…”
Section: Discussionmentioning
confidence: 55%
“…The positive outcomes of these and other pre-clinical studies are prompting human trials assaying the impact of NR supplementation on a variety of metabolic and exercise-related end-points in healthy adults, old persons, and persons with obesity, with disparate results so far [ 18 , 19 , 20 , 21 , 22 , 23 ]. Mechanistically, the benefits of NR have been linked to increased mitochondria abundance and oxidative function in key metabolic tissues through NAD + activation of SIRT1 [ 5 , 7 , 10 , 12 , 13 ], an enhancement of the differentiating capacity of adult progenitor cells [ 16 ], and effects on the gut microbiota [ 11 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…How these effects might be involved in the actions of ingested nutritional compositions is a topic of heightened interest. These issues are addressed head-on in a recent publication by Lozada-Fernández et al ( 4 ), where they consider the effects of the NAD + precursor nicotinamide riboside (NR) on the gut microbiome and investigate the contributions of the microbiome to the observed mitigating effects of NR in a mouse model of metabolic syndrome.…”
Section: Commentarymentioning
confidence: 99%
“…Lozada-Fernández et al ( 4 ) provide an intriguing investigation of this question. They ask if NR alters metabolism in the gut microbiome of mice during HFD treatment.…”
Section: Commentarymentioning
confidence: 99%